FINANCIAL MANAGEMENT AS A STRATEGIC BASIS FOR ENTERPRISE CRISIS MANAGEMENT - HAVLOVSKA, Nataliia; VLASIYK Іrina; SAMAR, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the implementation of financial management within the enterprise management system, taking into account the scale of operations, organizational structure, workforce composition, and financial resources. The content and organizational features of financial management are revealed across three types of enterprises – small, medium, and large. For each category, visual schemes of management structures are presented, and the functional responsibilities of key personnel are systematically detailed in tabular form. In small enterprises, financial management functions are primarily concentrated in the roles of the director and chief accountant. In contrast, medium and large enterprises establish more complex financial management systems that include specialized units responsible for planning, budgeting, financial analysis, tax planning, investment management, and other key areas. The study highlights that enterprise size affects not only the organization of financial departments but also the depth of analytics, the planning horizon, the implementation of IT solutions, and the level of staff specialization required. Special attention is given to the functional model of financial management, which integrates external environmental factors with internal managerial processes. This model is conceptualized as an information and analytical cycle comprising accounting, control, analysis, forecasting, planning, management, and decision implementation. Such an approach ensures adaptability of the enterprise management system to external dynamics and internal structural specifics, enhancing organizational resilience and competitiveness. Furthermore, in the context of financial instability and growing market uncertainty, the role of financial management expands to include enterprise adaptation. The ability to swiftly respond to changes, develop anti-crisis strategies, construct financial models, and apply forecasting mechanisms is emphasized as a critical factor for sustainable development and risk mitigation.